Diagnosis and Surgical Treatment of Thoracic Dorsal Arachnoid Web: A Report of Two Cases. (14th September 2020) - Inoue, Junichi; Miyakoshi, Naohisa; Hongo, Michio; Kobayashi, Takashi; Abe, Toshiki; Kikuchi, Kazuma; Abe, Eiji; Kasukawa, Yuji; Ishikawa, Yoshinori; Kudo, Daisuke; Kinoshita, Hayato; Kimura, Ryota; et al.
Abstract : Introduction. An arachnoid web (AW) is a relatively rare disease and shows clinical symptoms and radiological findings similar to those of an arachnoid cyst (AC) or spinal cord herniation (SCH). Since the operative procedures for an AW are generally different from those intrathecal disorders, correct preoperative differential diagnosis is important. The purposes of this study were to report the usefulness of magnetic resonance imaging (MRI) and computed tomography (CT) myelography for diagnosing AW and to show the histological findings and clinical results. Case Description. Two patients, a 79-year-old man and a 43-year-old woman, are presented. The primary diagnoses were AC with ossification of the ligamentum flavum and epidural hematoma, respectively, in previous hospitals. They were finally diagnosed by the characteristic MRI and CT myelogram finding called the "scalpel sign." Histological findings showed epithelial cells and fibrous tissue derived from arachnoid tissues and microcalcifications. After surgery, the scalpel sign has vanished, and aggravation of their symptoms was prevented. Conclusion. An AW is refractory, but early detection by MRI and CT myelography and early treatment improve outcomes after surgery.